2016
DOI: 10.1007/s00115-016-0116-y
|View full text |Cite
|
Sign up to set email alerts
|

Brennpunkt Notaufnahme

Abstract: The number of patients treated in hospital emergency departments in Germany has risen in recent years to approximately 20 million. This escalation also applies to the increasing numbers of patients presenting with neurological symptoms and diseases, which occur in approximately 20 % of emergency patients. In addition to patients with stroke, inflammatory or degenerative central nervous system (CNS) and peripheral nervous system (PNS) disorders who need urgent treatment, more and more patients with nonspecific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…12 Recently, criticism was raised regarding a lack of reliable discrimination, leading to a high percentage of patients triaged to ESI category 3. 18,19 In our cohort of patients with neurological signs and complaints and confirming data reported by Lange and coworkers, 20 we found a considerable number of patients receiving ESI category 2, because patients with seizures and suddenly occurring focal deficits regardless of onset are triaged to this level. From a neurological perspective, there is a highly relevant difference in acuity of a patient with a focal neurological deficit that has been present for 2 hrs or for 12 hrs, or between a patient with a first-ever seizure or a recurrent seizure and a history of epilepsy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…12 Recently, criticism was raised regarding a lack of reliable discrimination, leading to a high percentage of patients triaged to ESI category 3. 18,19 In our cohort of patients with neurological signs and complaints and confirming data reported by Lange and coworkers, 20 we found a considerable number of patients receiving ESI category 2, because patients with seizures and suddenly occurring focal deficits regardless of onset are triaged to this level. From a neurological perspective, there is a highly relevant difference in acuity of a patient with a focal neurological deficit that has been present for 2 hrs or for 12 hrs, or between a patient with a first-ever seizure or a recurrent seizure and a history of epilepsy.…”
Section: Discussionsupporting
confidence: 90%
“…Patients with highly acute neurological diseases formally do not qualify for the highest urgency level in ESI, as they rarely present in states requiring immediate life-saving interventions. In addition, vital signs, which in established triage systems take precedence over the time-is-brain concept, 20 in most cases do not convey neurological urgency. Cerebrovascular disease excellently illustrates this aspect: therapeutic options are time-limited and even long-term prognosis depends on the actual timing of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, various algorithms have been developed for the emergency evaluation of other neurological symptoms, most notably vertigo [ 10 ]. An overarching triage algorithm for patients with neurological complaints has been missing up to the development of HEINTS, which is all the more relevant since the representation of neurological symptoms in established general triage systems appears insufficient: on the one hand, a large number of patients fall into one of the more urgent categories with potential over-triage [ 16 ], on the other hand, patients are assigned to less acute categories when they present with atypical symptoms or when they are less severely affected [ 19 ]. In this regard, a refined approach to the patient with a neurological deficit should be taken not only regarding ED clinical evaluation and diagnostic work-up [ 23 ] but even prehospitally and during triage.…”
Section: Discussionmentioning
confidence: 99%
“…This two-faceted scenario is ideal for the application of a triage procedure since triage systems were developed to facilitate acuity assessment as well as to predict patient disposition and resource utilization [ 11 , 22 ]. However, neurological symptoms appear to be inadequately represented in established triage systems like the Manchester Triage System (MTS) or the Emergency Severity Index (ESI): While there are no dedicated investigations into the performance of currently used systems in neurological patients, Lange et al found that over 50% of ED neurological patients were triaged into ESI category 2, which allows for a door-to-doctor time of up to 10 min [ 16 ]. Granting this amount of latency in door-to-doctor time most likely impacts on the quality of acute care in many patients with neurological emergencies, most notably in acute ischemic stroke, where a door-to-needle time of 30 min or less [ 12 , 18 ] may be difficult to achieve under these circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Значительные изменения, происходящие в социальной, экономической и демографической структуре развитых стран сказываются в том числе и на ситуации в медицинском обслуживании населения. Непрерывно растет нагрузка на медучреждения и, в первую очередь, на службы экстренной и неотложной помощи; количество обращений за год в некоторых европейских странах превышает 20% от общей численности населения [1]. Это приводит к тому, что экстренное медицинское обслуживание в стационарах быстро развивается и приобретает все возрастающее значение не только с профессиональной медицинской точки зрения, но и с точки зрения экономической политики.…”
unclassified